Menander and the expectations of his audience - Ciesko, M (2004)
How can a dramatist writing in a highly conventional genre 'imitate life'? I develop various aspects of the hypothesis that the stereotypes of New Comedy were put to a varied dramatic use through being questioned, reacted against, or commented upon - always in ways that eventually upheld them in such an intricate and polyphonous process that spectators' demand for novelty was fully satisfied. The thesis contains four larger sections; each is in a different way a commentary on the extant plays and their conventions. Ch. I. 'Techniques of foreshadowing and character presentation in Menander's Aspis in the light of Greek dramatic traditions' In a running commentary on the chosen play I explore the problems of the spectators' expectations of what a newly staged play should be like, as they are shaped by the familiarity with the generic rules. The question of genre and its boundaries is particularly pronounced in this play since it chose Tragedy to carry its comic meaning. Ch. II. 'Conventions in the theatre of life: Menander's Stagecraft' and Ch. III. 'The Oikos as a Dramatic Space' Even in the conventionally fixed stage space Menander could recreate miniatures symbolic of real life experiences. Through exquisite plotting, he could allow his spectators an insight into the deep recesses of the house and the minds of its inhabitants. I show how fixed and unchanging setting becomes a dynamic force in moving Menander's plots ahead. Ch. IV. 'Familiar games and the poet's voice in self-advertisement.' How can a New Comedy playwright advertise and 'sell' to his audience a play if he works in a genre that does not destroy its Fiktion der Handlung? This highly conventional genre can, I claim, through both embracing and problematising its very conventionality express itself with irony and subtlety that is at least as effective as open self-praise by poets in comic genres that allow it.